2020
DOI: 10.48550/arxiv.2012.15531
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Colonoscopy Polyp Detection: Domain Adaptation From Medical Report Images to Real-time Videos

Abstract: Automatic colorectal polyp detection in colonoscopy video is a fundamental task, which has received a lot of attention. Manually annotating polyp region in a large scale video dataset is time-consuming and expensive, which limits the development of deep learning techniques. A compromise is to train the target model by using labeled images and infer on colonoscopy videos. However, there are several issues between the image-based training and video-based inference, including domain differences, lack of positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
0
0
Order By: Relevance
“…In Ivy-Net, a modified mix-up is utilized to generate training data by combining positive and negative video frames at the pixel level, which can learn domain-adaptive representations and augment positive samples. Experiments on collected datasets have demonstrated that Ivy-Net achieves state-of-the-art results and significantly improves the average precision of the polyp detection in colonoscopy videos [26][27][28]. It is not surprising that, if a model is trained with data from an older capsule, it may not yield the expected results when it is evaluated with a newer capsule, because the same distribution of data is not guaranteed.…”
Section: Colonoscopy Polyp Detection: Domain Adaptation From Medical ...mentioning
confidence: 99%
See 1 more Smart Citation
“…In Ivy-Net, a modified mix-up is utilized to generate training data by combining positive and negative video frames at the pixel level, which can learn domain-adaptive representations and augment positive samples. Experiments on collected datasets have demonstrated that Ivy-Net achieves state-of-the-art results and significantly improves the average precision of the polyp detection in colonoscopy videos [26][27][28]. It is not surprising that, if a model is trained with data from an older capsule, it may not yield the expected results when it is evaluated with a newer capsule, because the same distribution of data is not guaranteed.…”
Section: Colonoscopy Polyp Detection: Domain Adaptation From Medical ...mentioning
confidence: 99%
“…Laiz et al first proposed the concept of triplet loss function for domain adaptation in capsule endoscopy, and reported that it could improve the reading accuracy by improving the generalization of the datasets obtained from different systems [25]. Zhan et al improved the polyp detection in colonoscopy videos by using Ivy-Net to bridge the domain gap between colonoscopy images and real-time videos [28]. Celik et al applied a UDA framework for the segmentation of BE, which is a precancerous lesion [32].…”
Section: Perspective and Future Directionmentioning
confidence: 99%